THE FUNDAMENTALS OF ECONOMIC STABILITY AND SECURITY IN CENTRAL AND EASTERN EUROPE - Sobirjonova Kamola Abrorkhon kizi (Scholar Express Journals, 2023)
While opinions differ when reviewing factors of economic stability and development, there is clearly a common endorsement of the belief that economic stability is linked to security. Therefore, addressing the issue of security in Albania and Ukraine, speakers actually focused on the search for solutions to the severe economic problems of these countries. Indeed, “economic security is constructive - building a strong economy within” by opening of borders and “military security is defensive - keeping one’s enemies out”, as stated by David Snelbecker. This implies an eventual policy conflict - economic dependence from the “enemy” is undesirable, as it was during the cold war
Keywords: Foreign direct investment; economic growth; the United States